Imams in Western Europe Developments, Transformations, and Institutional Challenges - Hashas, Mohammed; de Ruiter, Jan-Jaap; Valdemar Vinding, Niels (Amsterdam University Press, 2018)
As European Muslims and Muslims in the Middle East diverge, imams in Europe have emerged as major agents of religious authority who shape Islam's presence in Western societies. This volume examines the theoretical and practical questions concerning the evolving role of imams in Europe. To what extent do imams act as intermediaries between European states and Muslim communities? Do states subsidise imam training? How does institutionalisation of Islam differ between European states?